The Effect of Cooperative Learning Student Team Achievement Division (STAD) Model on Student Learning Outcomes of Grade V of Elementary School of Sukajaya - dedie gustiawan; Hasan Bisri (Fakultas Agama Islam dan Pendidikan Guru, 2018)
This research is motivated by low learning outcomes of science in class V. Based on these problems, the researchers applies the model of learning STAD. The purpose of this study is to determine the effect of the application of STAD method to the result of science learning in SDN Sukajaya 01.The model used by the researcher is quasi experiment research with type nonequivalent control group design. The population in this research is all student of class V SD N Sukajaya 01with sampling technique of nonpropability sampling with saturated sample type consisting of two experiment class. Data colection technic are done by way of observation, test and documentation. Based on the result of t test at significance level a = 0,05 obtained thitung 3,33 while ttabel 2,00 so obtained thitung> ttable, this null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Based on the results of research that has been done, it can be concluded that there is influence of learning model STAD to science learning outcomes of class V student. STAD science learning outcomes are better compared to conventional class group.